Functional Characterization of Dual-Initiation Codon-Derived V2 Proteins in Tomato Yellow Leaf Curl Virus - Zhiyuan Wang; Pan Gong; Siwen Zhao; Fangfang Li; Xueping Zhou (Agronomy, 2025)
Tomato yellow leaf curl virus (TYLCV) is a highly destructive pathogen of global tomato crops. The open reading frame (ORF) of TYLCV V2 contains two initiation codons (ATG1/V2-1 and ATG2/V2-2), producing distinct protein isoforms. Using custom antibodies, we confirmed V2-1 and V2-2 expression in infected Nicotiana benthamiana and tomato plants. Deletion mutants revealed their specialized roles: V2-1 was indispensable for viral replication and systemic spread—its loss severely reduced pathogenicity and genome accumulation. V2-2 acted as an auxiliary factor, and its deletion attenuated symptoms but kept the virus infection. Host-specific effects were observed—V2-1 deletion led to lower viral DNA/coat protein levels in N. benthamiana than in tomato, suggesting host-dependent regulation. Mutant viruses declined progressively in tomato, indicating host defense clearance. Heterologous co-expression of both isoforms via potato virus X induced systemic necrosis in N. benthamiana, demonstrating functional synergy between isoforms. Both initiation codons were essential for V2-mediated suppression of transcriptional gene silencing (TGS) and post-transcriptional gene silencing (PTGS). This study uncovers the mechanistic divergence of V2 isoforms in TYLCV infection, highlighting their collaborative roles in virulence and host manipulation. The findings advance understanding of geminivirus coding complexity and offer potential targets for resistance strategies.